Design, synthesis, and pharmacological evaluation of 2-amino-5-nitrothiazole derived semicarbazones as dual inhibitors of monoamine oxidase and cholinesterase: effect of the size of aryl binding site - Rati K. P. Tripathi; Vishnu M. Sasi; Sukesh K. Gupta; Sairam Krishnamurthy; Senthil R. Ayyannan (Taylor and Francis Ltd, 2017)
A series of 2-amino-5-nitrothiazole derived semicarbazones were designed, synthesised and investigated for MAO and ChE inhibition properties. Most of the compounds showed preferential inhibition towards MAO-B. Compound 4, (1-(1-(4-Bromophenyl)ethylidene)-4-(5-nitrothiazol-2-yl)semicarbazide) emerged as lead candidate (IC50¼ 0.212 mM, SI ¼ 331.04) against MAO-B; whereas compounds 21 1-(5-Bromo-2-oxoindolin-3-ylidene)-4-(5-nitrothiazol-2-yl)semicarbazide (IC50¼ 0.264 mM) and 17 1-((4-Chlorophenyl) (phenyl)- methylene)-4-(5-nitrothiazol-2-yl)semicarbazide (IC50¼ 0.024 mM) emerged as lead AChE and BuChE inhibitors respectively; with activity of compound 21 almost equivalent to tacrine. Kinetic studies indicated that compound 4 exhibited competitive and reversible MAO-B inhibition while compounds 21 and 17 showed mixed-type of AChE and BuChE inhibition respectively. Docking studies revealed that these compounds were well-accommodated within MAO-B and ChE active sites through stable hydrogen bonding and/or hydrophobic interactions. This study revealed the requirement of small heteroaryl ring at amino terminal of semicarbazone template for preferential inhibition and selectivity towards MAO-B. Our results suggest that 5-nitrothiazole derived semicarbazones could be further exploited for its multi-targeted role in development of anti-neurodegenerative agents
Keywords: 2-Amino-5-nitrothiazole; monoamine oxidase; Cholinesterase; dual inhibitors; molecular docking